Conductive hydrogel, gel ball and preparation method and application thereof
By not using strong oxidants, the hydrogen bonding between pyrrole and natural polymer is used to form a conductive hydrogel, which solves the solubility of polypyrrole in polar solvents and the brittleness of conductive hydrogels, and realizes the conductive hydrogel The structural tightness and mechanical properties are improved.
Patent Information
- Application Number
- CN202310293433.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-24
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2043-03-24
AI Technical Summary
Polypyrrole has poor solubility in polar solvents and the brittleness of conductive hydrogels containing PPy, and the conductive polymer has few active groups and is difficult to interact well with tissues or cells.
By not adding strong oxidants, the higher solubility of pyrrole in the solvent and the hydrogen bonding with natural polymers are used to form a conductive hydrogel with a tissue-acceptable carrier, improving its structural tightness and mechanics. performance.
The conductive hydrogel has a tighter structure and excellent mechanical properties, avoiding the denaturation of matrix hydrogel materials and oxidant residual toxicity caused by strong oxidants, and improving the sensitivity, stability and mechanical properties of conductive hydrogels.
Smart Images

Figure CN116284861B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a conductive hydrogel, a gel ball and a preparation method and application thereof. Background Art
[0002] Conductive hydrogels are highly hydrated three-dimensional networks generated by incorporating conductive polymers, nanoparticles, and other conductive materials into polymer hydrogels. Combining the excellent properties of conductive materials with the highly tunable physical and biochemical properties of hydrogel matrix materials can form new conductive hydrogels. Conductive hydrogels that have been reported include incorporating conductive materials (such as gold and silver nanoparticles, graphene, and carbon nanotubes) and various conductive polymers (such as polyaniline, polypyrrole, and poly(3,4-ethylenedioxythiophene)) into the hydrogel matrix network. These conductive composite hydrogels have high swelling properties, tunable mechanical properties, and the ability to support cell growth in vitro and in vivo. Recently, biocompatible conductive hydrogels have been studied for various biomedical applications, such as tissue engineering, drug delivery, biosensors, flexible electronic devices, and other implantable medical devices.
[0003] Polypyrrole (PPy) is a conductive polymer that has been widely used as a conductive material for various sensors due to its ease of synthesis, tunable mechanical properties, environmental stability, and good biocompatibility. In addition, it can also be used in drug delivery systems and bioelectrodes, as well as the engineering of cardiac tissue structures and artificial muscles. Yang et al. achieved the combination of PPy and hyaluronic acid (HA) by coupling N-(3-aminopropyl) pyrrole to HA polymer chains. The results showed that the elastic modulus and conductivity of the conductive hydrogel increased with increasing PPy concentration. PPy has become a very popular conductive polymer for the manufacture of biocompatible conductive hydrogels with excellent stimulus-responsive properties and high thermal stability. PPy can also be used for tissue regeneration of electrically responsive tissues such as nerves and heart.
[0004] However, the poor solubility of PPy in polar solvents and the brittleness of PPy-containing conductive hydrogels need to be addressed. In addition, conductive polymers have few active groups, such as -NH2 and -OH, that interact with tissues or cells, so the preparation of PPy conductive hydrogels that combine biocompatibility with good mechanical and electrical properties remains challenging.
[0005] In order to improve the mechanical properties of conductive polymer-based hydrogels, conductive polymers have been blended with high molecular weight polymers such as hyaluronic acid, cellulose and chitosan. However, the conductivity of the conductive hydrogel network decreases with the addition of insulating polymer (high molecular weight polymer) blocks. The strong oxidants (such as ferric chloride, ammonium persulfate, etc.) added in the commonly used method of synthesizing polypyrrole can easily cause the denaturation of the base polymer if not properly controlled, which is even more unfavorable for the formation of conductive hydrogels with excellent mechanical properties. Summary of the invention
[0006] The purpose of the present invention is to provide a conductive hydrogel and gel ball with excellent performance, and a preparation method and application thereof.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is:
[0008] The invention discloses a conductive hydrogel, which is formed by cross-linking pyrrole and a natural high molecular polymer and has a carrier acceptable to tissues. The conductive hydrogel does not contain a strong oxidant.
[0009] Usually, when preparing polypyrrole, in order to promote polymerization, a strong oxidant is often used as an initiator. The present invention does not add a strong oxidant, and utilizes the higher solubility of pyrrole in the solvent and the hydrogen bonding between the natural high molecular polymer. While preparing the conductive hydrogel network, a polypyrrole network can be formed, which makes the structure of the conductive hydrogel more compact and has excellent mechanical properties; on the other hand, it avoids the denaturation of the matrix hydrogel material and the toxicity of the residual oxidant caused by the strong oxidant. Compared with pure polypyrrole coating conductive hydrogel (such as the coating of polypyrrole on the surface of silk fibroin material), the mechanical properties are better; compared with the conductive hydrogel simply doped with polypyrrole particles, the conductive network distribution is more uniform, and the sensitivity and stability of the conductive hydrogel detection signal are better.
[0010] Preferably, the conductive hydrogel contains 0 to 500 ppm lithium bromide and 0 to 500 ppm sodium carbonate.
[0011] Preferably, the strong oxidant includes one or more of ferric chloride, ammonium persulfate, potassium persulfate, and sodium persulfate.
[0012] Preferably, the natural high molecular polymer is one or more of silk, cellulose, hyaluronic acid and chitosan. The silk is preferably degummed silk, further degummed for 5 minutes to 24 hours, and further degummed for 30 to 120 minutes. The degumming system of silk includes but is not limited to a sodium carbonate system.
[0013] Preferably, the mass volume ratio of the natural high molecular polymer to the pyrrole is 1 g: (40-200000) μL.
[0014] In some embodiments, when the natural high molecular polymer is silk, the mass volume ratio of the natural high molecular polymer to the pyrrole is 1 g: (100-2500) μL.
[0015] Further preferably, the mass volume ratio of the natural high molecular polymer to the pyrrole is 1g:(200-500)μL, for example, 1g:200μL, 1g:250μL, 1g:300μL, 1g:350μL, 1g:400μL, 1g:450μL, 1g:500μL, etc.
[0016] In some embodiments, when the natural polymer is hyaluronic acid, the mass volume ratio of the natural polymer to the pyrrole is 1g:(40-2000)μL, for example, 1g:40μL, 1g:200μL, 1g:500μL, 1g:700μL, 1g:1000μL, 1g:1200μL, 1g:1500μL, 1g:1700μL, 1g:2000μL.
[0017] In some embodiments, when the natural polymer is cellulose, the mass volume ratio of the natural polymer to the pyrrole is 1g:(400-200000)μL, for example, 1g:400μL, 1g:1000μL, 1g:5000μL, 1g:10000μL, 1g:30000μL, 1g:50000μL, 1g:80000μL, 1g:100000μL, 1g:150000μL, 1g:200000μL, etc.
[0018] In some embodiments, when the natural polymer is chitosan, the mass volume ratio of the natural polymer to the pyrrole is 1g:(40-2000)μL, for example, 1g:40μL, 1g:200μL, 1g:500μL, 1g:700μL, 1g:1000μL, 1g:1200μL, 1g:1500μL, 1g:1700μL, 1g:2000μL.
[0019] Preferably, the cross-linking is performed in the presence of a cross-linking agent.
[0020] Preferably, the cross-linking agent is selected from one or more diglycidyl ethers.
[0021] More preferably, the diglycidyl ethers include diglycidyl ether, 1,4-butanediol diglycidyl ether, 1,3-diglycidyl ether glycerol, bisphenol A diglycidyl ether and its derivatives, resorcinol diglycidyl ether, tris(4-hydroxyphenyl)methane triglycidyl ether and neopentyl glycol diglycidyl ether.
[0022] Preferably, the mass volume ratio of the natural high molecular polymer to the cross-linking agent is 1 g: (0.5-400000) μL.
[0023] In some embodiments, when the natural high molecular polymer is silk, the mass volume ratio of the natural high molecular polymer to the cross-linking agent is 1 g: (0.5-1000) μL.
[0024] Further preferably, the mass volume ratio of the natural high molecular polymer to the cross-linking agent is 1g:(150-300)μL, for example, 1g:150μL, 1g:175μL, 1g:200μL, 1g:225μL, 1g:250μL, 1g:300μL.
[0025] In some embodiments, when the natural polymer is hyaluronic acid, the mass volume ratio of the natural polymer to the cross-linking agent is 1g:(80-4000)μL, for example, 1g:80μL, 1g:500μL, 1g:1000μL, 1g:1500μL, 1g:2000μL, 1g:2500μL, 1g:3000μL, 1g:3500μL, 1g:4000μL.
[0026] In some embodiments, when the natural high molecular polymer is cellulose, the mass volume ratio of the natural high molecular polymer to the cross-linking agent is 1g:(800-400000)μL, for example, 1g:800μL, 1g:5000μL, 1g:10000μL, 1g:50000μL, 1g:100000μL, 1g:150000μL, 1g:200000μL, 1g:250000μL, 1g:300000μL, 1g:350000μL, 1g:400000μL, etc.
[0027] In some embodiments, when the natural polymer is chitosan, the mass volume ratio of the natural polymer to the cross-linking agent is 1g:(80-4000)μL, for example, 1g:80μL, 1g:500μL, 1g:1000μL, 1g:1500μL, 1g:2000μL, 1g:2500μL, 1g:3000μL, 1g:3500μL, 1g:4000μL.
[0028] The second object of the present invention is to provide a method for preparing a conductive hydrogel, comprising the following steps:
[0029] (1) preparing a solution containing pyrrole, natural high molecular polymer and lithium bromide;
[0030] (2) adding a crosslinking agent to the solution to form a conductive hydrogel by crosslinking;
[0031] The conductive hydrogel does not contain a strong oxidant.
[0032] Preferably, the lithium bromide is fed in the form of a lithium bromide aqueous solution, and the mass volume ratio of the natural high molecular polymer to the lithium bromide aqueous solution is (0.5-400) mg:1 mL.
[0033] More preferably, the mass volume ratio of the natural high molecular polymer to the lithium bromide aqueous solution is (150-350) mg:1 mL.
[0034] Preferably, the concentration of the lithium bromide aqueous solution is 1-10M.
[0035] More preferably, the concentration of the lithium bromide aqueous solution is 2-9.8M.
[0036] Preferably, the step (1) specifically comprises: adding the natural high molecular polymer soaked in pyrrole into the lithium bromide aqueous solution, dissolving it at 4 to 80° C. for 10 min to 72 h, to obtain the solution.
[0037] More preferably, the dissolution temperature is 25 to 70°C.
[0038] More preferably, the dissolution time is 1 to 12 hours.
[0039] Preferably, in step (2), the cross-linking temperature is 4 to 80°C.
[0040] More preferably, the crosslinking temperature is 25 to 70°C.
[0041] Preferably, the cross-linking time is 10 min to 72 h.
[0042] More preferably, the cross-linking time is 1 to 12 hours.
[0043] Preferably, the preparation method further comprises dialyzing the conductive hydrogel in deionized water, PBS or a drug solution before use.
[0044] The third object of the present invention is to provide a method for preparing conductive gel balls, comprising mixing the above solution with a crosslinking agent, adding the mixture to an oil phase system, and performing a crosslinking reaction under stirring conditions.
[0045] Preferably, the volume ratio of the mixed solution of the solution and the cross-linking agent to the oil phase system is 1:(5-500), further 1:(5-100).
[0046] Preferably, the stirring speed is 100-1000 rpm.
[0047] The fourth object of the present invention is to provide a conductive gel ball prepared by the preparation method as described above.
[0048] A fifth object of the present invention is to provide use of the conductive hydrogel or conductive gel ball as described above in electrode coating, drug delivery or tissue engineering.
[0049] The conductive hydrogel or conductive gel ball prepared by the present invention has hydrogen bonding between polypyrrole and natural high molecular polymer molecules, which makes the silk protein conductive hydrogel gel structure more compact, has excellent mechanical properties, and good biocompatibility, so that it can be used in vivo and in vitro. It can be used as a carrier for antibacterial and anti-inflammatory drugs, and has expanded its application to tissue engineering and integrated coating of instruments.
[0050] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:
[0051] The present invention does not need to add strong oxidants. By forming a polypyrrole network while preparing the conductive hydrogel network, on the one hand, the conductive network distribution is more uniform, the structure of the conductive hydrogel is more compact, and the sensitivity, stability and mechanical properties of the conductive hydrogel are improved; on the other hand, the problems of matrix hydrogel material denaturation and residual toxicity of the oxidant caused by strong oxidants are avoided. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 This is a physical picture of the conductive hydrogel, in which the lithium bromide concentration of the reaction system is fixed at 9.3M, the lithium bromide-to-silk bath ratio is 200mg / mL, the dissolution temperature is 60°C, and the reaction time is 1.5h, and the ratio of silk fibroin (SF) and pyrrole (Py) in the reaction system is changed;
[0053] Figure 2 Schematic diagram of the resistance change rate of the conductive hydrogel;
[0054] Figure 3 Schematic diagram of compression modulus of conductive hydrogel;
[0055] Figure 4 are morphological images of hydrogels, where a and b are hydrogels without polypyrrole, and c and d are polypyrrole conductive hydrogels;
[0056] Figure 5 Schematic diagram of the strain rate (left) and elastic modulus (right) of the hydrogel;
[0057] Figure 6 Schematic diagram of the conductivity change of the hydrogel made of hyaluronic acid as the base material;
[0058] Figure 7 This is a real photo of a hydrogel made of carboxymethyl cellulose as the base material;
[0059] Figure 8 Schematic diagram of hydrogel strain made of chitosan as the base material. DETAILED DESCRIPTION
[0060] The present invention is further described below in conjunction with the examples. However, the present invention is not limited to the following examples. The implementation conditions used in the examples can be further adjusted according to the different requirements of specific use, and the implementation conditions not specified are conventional conditions in the industry. The technical features involved in each embodiment of the present invention can be combined with each other as long as they do not conflict with each other.
[0061] Example 1
[0062] (1) Weigh 30g of raw silk and 25.44g of anhydrous sodium carbonate for later use, measure 12L of deionized water and pour it into a stainless steel bucket, and heat it with an induction cooker. When the deionized water is about to boil, add the weighed anhydrous sodium carbonate, continue heating and stirring until boiling, so that the anhydrous sodium carbonate is fully dissolved, then add the weighed raw silk, keep boiling for 30 minutes (i.e., degumming time), and stir every 5 minutes to dissolve the sericin on the surface of the raw silk. Rub the degummed raw silk with deionized water for 4 times to fully remove the sericin on the surface of the raw silk, and finally wring the degummed silk and place it in a fume hood to dry overnight.
[0063] (2) Measure 1 mL of 9.3 M lithium bromide into an epoxied tube, add 0.2 g of degummed silk fully soaked in 100 μL of pyrrole into the tube, and dissolve it at 60°C. After dissolving for 1.5 h to obtain lithium bromide silk solution, add 40 μL of 1,4-butanediol diglycidyl ether (BDDE), mix well and remove bubbles, place in a 60°C oven for reaction, and let stand for 3 h to form a gel.
[0064] Comparative Example 1
[0065] The difference from Example 1 is the above step (2):
[0066] Weigh 5.6 mg of ferric chloride hexahydrate and dissolve it in 1 mL of 9.3 M lithium bromide in an ep tube. After fully soaking 0.2 g of degummed silk in 50 μL of pyrrole, add the degummed silk into the tube and fully soak it in the mixed solution of lithium bromide and ferric chloride hexahydrate. Dissolve it at 60°C for 1.5 hours to obtain lithium bromide silk solution. Add 40 μL of BDDE, mix well and remove bubbles. Place it in a 60°C oven for reaction and let it stand for 3 hours to form a gel.
[0067] The conductive hydrogel obtained by the two methods of embodiment 1 and comparative example 1 is placed in deionized water, dialyzed for 3 days, changed water 7-8 times in total, and observed the hydrogel state.Research finds that both methods can form polypyrrole conductive hydrogel, and the gelling effect is good, but the introduction of strong oxidants (ferric chloride hexahydrate, ammonium persulfate, etc.) is improperly easily caused to denature silk fibroin, which can cause the cross-linking agent to be unable to find suitable cross-linking sites, thereby causing the hydrogel to be unshaped.In addition, using strong oxidants can also produce irritation and corrosivity to the skin and mucous membranes, bringing a series of negative effects.Based on the above reasons, the inventor chooses not to add the simple operation of strong oxidants, utilizes the oxidizability of lithium bromide to synthesize polypyrrole in the presence of silk fibroin, and because silk fibroin has a highly stretched structure in lithium bromide, exposes more reactive groups, thereby giving more space for cross-linking reaction, plus the strong hydrogen bond existing between polypyrrole and silk fibroin, so that cross-linking reaches a better effect.
[0068] Example 2
[0069] Weigh 30g of raw silk and 25.44g of anhydrous sodium carbonate for later use. Pour 12L of deionized water into a stainless steel bucket and heat it with an induction cooker. When the deionized water is about to boil, add the weighed anhydrous sodium carbonate, continue heating and stirring until boiling, so that the anhydrous sodium carbonate is fully dissolved, then add the weighed raw silk, keep boiling and cook to dissolve the sericin on the surface of the raw silk. Rub the degummed raw silk with deionized water to fully remove the sericin on the surface of the raw silk. Finally, wring the degummed silk and place it in a fume hood to dry overnight.
[0070] Conductive hydrogels were prepared according to different degumming times (boiling times): 5min, 10min, 20min, 30min, 40min, 50min, 60min, 70min, 80min, 90min, 100min, 110min, and 120min. The results showed that the above conditions can form gels in the subsequent steps, and the good morphology can be applied to subsequent tests and sensing performance research. As the degumming time increases, the degumming rate increases, the molecular weight will also decrease, more groups and cross-linking sites will be exposed, the cross-linking efficiency of the conductive hydrogel will increase, and it will show better elasticity and mechanical stability.
[0071] Example 3
[0072] The lithium bromide concentration, lithium bromide-to-silk bath ratio, the ratio of silk fibroin (i.e., degummed silk) to pyrrole, dissolution temperature and dissolution time were tested.
[0073] Lithium bromide concentration: 1M, 2M, 3M, 4M, 5M, 6M, 7M, 8M, 9.3M, 9.5M, 9.8M.
[0074] Lithium bromide solution bath ratio (mass volume ratio of degummed silk and lithium bromide solution): 0.5mg / mL, 1mg / mL, 4mg / mL, 7mg / mL, 10mg / mL, 15mg / mL, 20mg / mL, 25mg / mL, 50mg / mL, 75mg / mL, 100mg / mL, 120mg / mL, 125mg / mL, 150mg / mL, 175mg / mL, 200mg / mL, 250mg / mL, 300mg / mL, 350mg / mL, 400mg / mL.
[0075] The ratio of silk fibroin (i.e. degummed silk) and pyrrole: 1:100 g / μL, 1:125 g / μL, 1:150 g / μL, 1:200 g / μL, 1:250 g / μL, 1:300 g / μL, 1:375 g / μL, 1:400 g / μL, 1:500 g / μL, 1:1000 g / μL, 1:2500 g / μL, 1:5000 g / μL, 1:7500 g / μL.
[0076] Dissolving temperature (or silk melting temperature): 4℃, 10℃, 25℃, 37℃, 60℃, 80℃, 100℃.
[0077] Dissolution time (or silk dissolving time): 10 minutes, 20 minutes, 30 minutes, 40 minutes, 1 hour, 1.5 hours, 3 hours, 6 hours, 12 hours, 18 hours, 24 hours, 36 hours, 48 hours, 72 hours.
[0078] ① The lithium bromide-to-silk bath ratio of the reaction system was fixed at 200 mg / mL, the ratio of silk fibroin to pyrrole was 1 g / 500 μL, the dissolution temperature was 60°C, and the dissolution time was 1.5 h, and the concentration of lithium bromide in the reaction system was changed.
[0079] 1 mL of 1 M, 2 M, 3 M, 4 M, 5 M, 6 M, 7 M, 8 M, 9.3 M, 9.5 M, and 9.8 M lithium bromide was measured and placed in an ep tube, and 0.2 g of degummed silk soaked with 100 μL of pyrrole (degumming time was 90 min) was added, and then dissolved at 60 ° C for 1.5 h to obtain lithium bromide silk solution. Then 40 μL of BDDE was added to react, mixed evenly, placed in a 60 ° C oven, and allowed to stand for 3 h to form a gel, and the hydrogel state of each component and the compression modulus after dialysis were observed.
[0080] The study found that the color of the hydrogel became darker, and the hydrogel had a certain degree of formability when the lithium bromide concentration was 9.3M, 8M, 7M, 6M, and 5M. The compression modulus of the hydrogel with different lithium bromide concentrations decreased as the lithium bromide concentration decreased, and the compression modulus of the hydrogel was the largest when the lithium bromide concentration was 9.3M.
[0081] From the compression modulus test results, it can be seen that when the lithium bromide concentration is 9.3M, the hydrogel morphology is the best and the compression modulus is the highest; when the lithium bromide concentration is in the range of 1-10M, a relatively ideal conductive hydrogel can be obtained; in the range of 2-9.8M, the performance of silk fibroin hydrogel is even better.
[0082] ② The lithium bromide concentration of the reaction system was fixed at 9.3 M, the lithium bromide-to-silk bath ratio was 200 mg / mL, the dissolution temperature was 60°C, and the reaction time was 1.5 h, and the ratio of silk fibroin (SF) and pyrrole (Py) in the reaction system was changed.
[0083] According to the ratio of silk fibroin to pyrrole of 1:100g / μL, 1:125g / μL, 1:150g / μL, 1:200g / μL, 1:250g / μL, 1:300g / μL, 1:375g / μL, 1:400g / μL, 1:500g / μL, 1:1000g / μL, 1:2500g / μL, 1:5000g / μL, 1:7500g / μL, 0.2g silk fibroin was soaked with pyrrole, and then placed in 1mL9.3M lithium bromide solution, dissolved at 60℃, and the dissolution time was 1.5h to obtain lithium bromide silk solution. Then 40μL of BDDE was added to react, mixed evenly, placed in a 60℃ oven, and allowed to stand for 3h to form gel, and the state of each group of silk solution was observed.
[0084] The study found that Figure 1 As shown in the figure, with the increase of pyrrole addition amount, the color of the silk solution became darker. When the ratio of silk fibroin to pyrrole reached 1:2500 g / μL, the silk dissolving effect of lithium bromide was affected, and the silk fibroin aggregated together and was not completely dissolved, probably because of the excessive content of oily pyrrole.
[0085] The fixed pyrrole content showed better silk dissolving effect as the proportion of silk protein increased. After adding the crosslinker, the hydrogels all had a certain degree of formability. When the silk protein and pyrrole were 1:200g / μL, the compression modulus of the gel was the largest and the conductivity was the highest. In the range of 1:100g-1:2500g / μL, relatively ideal conductive hydrogels could be obtained; in the range of 1:200-1:500g / μL, the performance of silk protein hydrogel was even better.
[0086] ③ The reaction system was fixed with lithium bromide concentration of 9.3M, lithium bromide silk bath ratio of 200mg / mL, silk fibroin and pyrrole ratio of 1g / 200μL, dissolution temperature of 60℃, and the dissolution time was varied.
[0087] 1mL of 9.3M lithium bromide was measured in ep tubes, 0.2g of degummed silk soaked with 100μL pyrrole was added, and the mixture was dissolved at 60℃ for 10 minutes, 20 minutes, 30 minutes, 40 minutes, 1 hour, 1.5 hours, 3 hours, 6 hours, 12 hours, 18 hours, 24 hours, 36 hours, 48 hours, and 72 hours to obtain lithium bromide silk solution. Then 40μL of BDDE was added to react, mixed evenly, placed in a 60℃ oven, and allowed to stand for 3h to form gel, and the gel state of each component and the compression modulus after dialysis were observed.
[0088] The study found that when the dissolution time was 10 minutes, 20 minutes, 30 minutes, 40 minutes, 1 hour, 1.5 hours, 3 hours, and 6 hours, there was not much difference in the conductive hydrogels of each group, and all had a certain degree of formability. As the dissolution time increased, there was no significant difference in the compression modulus of the hydrogel. When the dissolution time was 10 minutes, the complete dissolution of the silk fibroin could be seen, and within the range of 10 minutes to 24 hours, a relatively ideal conductive hydrogel could be obtained. Within the range of 10 minutes to 6 hours, the performance of the conductive hydrogel was even better.
[0089] ④ The lithium bromide concentration of the reaction system was fixed at 9.3M, the ratio of silk fibroin to pyrrole was 1g / 200μL, the dissolution temperature was 60℃, and the dissolution time was 1.5h, and the lithium bromide-silk bath ratio of the reaction system was changed.
[0090] 1mL of 9.3M lithium bromide was measured in ep tubes respectively, and added to the degummed silk soaked with 100μL pyrrole according to the lithium bromide silk bath ratio of 0.5mg / mL, 1mg / mL, 4mg / mL, 7mg / mL, 10mg / mL, 15mg / mL, 20mg / mL, 25mg / mL, 50mg / mL, 75mg / mL, 100mg / mL, 120mg / mL, 125mg / mL, 150mg / mL, 175mg / mL, 200mg / mL, 250mg / mL, 300mg / mL, 350mg / mL, and 400mg / mL, and then dissolved at 60℃ for 1.5h to obtain lithium bromide silk solution. Then 40μL of BDDE was added to react, mixed evenly, placed in a 60℃ oven, and allowed to stand for 3h to form gel, and the gel state of each component, compression modulus after dialysis, and compression resistance change rate were observed.
[0091] The study found that the gelling effect under the above conditions is relatively good, see Figure 3(SF@PPy-20 corresponds to 200mg / mL lithium bromide bath ratio, SF@PPy-25 corresponds to 250mg / mL lithium bromide bath ratio, and SF@PPy-30 corresponds to 300mg / mL lithium bromide bath ratio). The compression modulus of hydrogels with different lithium bromide concentration bath ratios increases with the increase of bath ratio, and the change rate of compression resistance shows the same law as the compression modulus. In the range of 0.5-400mg / mL, relatively ideal conductive hydrogels can be obtained; in the range of 150-350mg / mL, the performance of conductive hydrogels is even better.
[0092] The compression resistance change rate of some hydrogels in this example is shown in Figure 2 (Among them, 15% corresponds to 150 mg / mL lithium bromide dissolved silk bath ratio, 20% corresponds to 200 mg / mL lithium bromide dissolved silk bath ratio, 25% corresponds to 250 mg / mL lithium bromide dissolved silk bath ratio, 30% corresponds to 300 mg / mL lithium bromide dissolved silk bath ratio, the horizontal axis represents the ratio of silk fibroin and pyrrole, among which 10:1 corresponds to 1:100 g / μL, 10:1.5 corresponds to 1:150 g / μL, 10:2 corresponds to 1:200 g / μL, 10:2.5 corresponds to 1:250 g / μL, 10:3 corresponds to 1:300 g / μL), the greater the resistance change rate, the more obvious the change in the electrical signal generated by the conductive material.
[0093] Example 4
[0094] The ratio of silk fibroin to BDDE and the temperature and time of the reaction system were tested. The morphology was observed using an electron microscope and its compression modulus was tested.
[0095] The ratio of silk fibroin to BDDE: 1g: 0.2μL, 1g: 0.5μL, 1g: 0.75μL, 1g: 1μL, 1g: 2μL, 1g: 5μL, 1g: 10μL, 1g: 20μL, 1g: 32.5μL, 1g: 50μL, 1g: 100μL, 1g: 120μL, 1g: 150μL, 1g: 300μL, 1g: 500μL, 1g: 750μL, 1g: 1000μL.
[0096] Reaction temperature: -20℃, 0℃, 4℃, 25℃, 37℃, 60℃, 80℃.
[0097] Reaction time: 1 minute, 3 minutes, 5 minutes, 7 minutes, 10 minutes, 20 minutes, 30 minutes, 40 minutes, 1 hour, 1.5 hours, 3 hours, 6 hours, 12 hours, 18 hours, 24 hours, 36 hours, 48 hours.
[0098] (1) 1 mL of 9.3 M lithium bromide was measured and placed in an epoxide tube, and 0.2 g of degummed silk soaked in 100 μL of pyrrole (degumming time was 90 min) was added, and the mixture was dissolved at 60°C for 1.5 h to obtain a lithium bromide silk solution.
[0099] Then, BDDE was added according to the ratio of silk fibroin to BDDE (1g: 0.2μL, 1g: 0.5μL, 1g: 0.75μL, 1g: 1μL, 1g: 2μL, 1g: 5μL, 1g: 10μL, 1g: 20μL, 1g: 32.5μL, 1g: 50μL, 1g: 100μL, 1g: 120μL, 1g: 150μL, 1g: 300μL, 1g: 500μL, 1g: 750μL, 1g: 1000μL), the mixture was mixed evenly, placed in an oven at 60°C, and allowed to stand for 3 hours to form a gel. The hydrogel state of each component and the compression modulus after dialysis were observed.
[0100] The results showed that when the ratio of silk fibroin to BDDE increased from 1g:32.5μL to 1g:200μL, the cross-linking efficiency of silk fibroin increased with the increase of BDDE addition. When the ratio of silk fibroin to BDDE was lower than 1g:200μL, part of the uncross-linked silk fibroin was wrapped in the chemical cross-linked hydrogel to form a physical cross-linked hydrogel, which reduced the light transmittance of the hydrogel. When the amount of BDDE added was further increased, the cross-linking efficiency of silk fibroin decreased. When the reaction concentration of silk fibroin was 200mg / mL, the ratio of silk fibroin to BDDE was 1g:200μL, which was the best reaction condition. In the range of silk fibroin to BDDE of 1g:0.5μL-1000μL, relatively ideal conductive hydrogels could be obtained. In the range of 1g:0.5μL-500μL, the performance of conductive hydrogel was even better.
[0101] (2) The difference from the above (1) is that the ratio of silk fibroin to BDDE was fixed at 1 g:200 μL, and the reaction time was changed.
[0102] The results show that when the reaction time is 1, 3, 6, and 24 hours, there is not much difference in the hydrogels of each group, and all have a certain degree of formability. As the reaction time increases, the hydrogel yield does not change much. The comprehensive yield and compression modulus test results show that as the reaction time increases, the yield and compression modulus of the gel are not much different. Cross-linking is completed when the reaction time is 1 hour, but the yield and compression modulus are the largest when the reaction time is 3 hours. In the range of 3 minutes to 24 hours, relatively ideal silk fibroin hydrogels can be obtained. In the range of 3 minutes to 12 hours, the performance of silk fibroin hydrogel is even better.
[0103] (3) The difference from the above (1) is that the ratio of silk fibroin to BDDE was fixed at 1 g:200 μL, and the reaction temperature was changed.
[0104] When the reaction temperature is 25℃, 37℃, 60℃, and 80℃, there is not much difference between the groups of hydrogels, and all have certain formability. As the reaction temperature increases, the hydrogel cross-links more quickly and completely, and the compression modulus does not change much. The conductive hydrogel prepared at a reaction temperature of 60℃ is most suitable for subsequent research.
[0105] See also Figure 4 The conductive hydrogel that meets the above conditions (shown in Figures c and d, the preparation method of the hydrogel refers to Example 1) and the pure silk fibroin hydrogel without pyrrole (shown in Figures a and b, the preparation method of the hydrogel refers to Example 1, the difference from Example 1 is that no pyrrole is added) are dialyzed and freeze-dried, and the cross-sectional morphology is observed after being broken by liquid nitrogen and sprayed with gold. It can be seen that there is no obvious difference in the structure of the two, but the conductive silk fibroin gel with pyrrole added has a denser structure, indicating that the presence of polypyrrole inhibits the growth of pores, confirming that there is a hydrogen bond between pyrrole and silk fibroin, resulting in a more dispersed stress applied to the conductive gel and a larger compression modulus.
[0106] See also Figure 5 , the conductive hydrogel (SF / PPy) is superior to the hydrogel (SF) without pyrrole added in terms of both elastic modulus and strain rate.
[0107] Example 5
[0108] Pure water and PBS dialysis can meet the biosafety requirements of conductive hydrogels after multiple changes of solution, and cells can proliferate and grow on the gel. The dialysis solution can also be replaced with drug solutions, such as antibacterial drugs (nanosilver, nanozinc oxide and antibiotics) and anti-inflammatory drugs (ibuprofen, berberine, etc.). In the dialysis process, the conductive hydrogel is given more functions, and the porous network in the gel is used to fully absorb the drug solution for in vitro and in vivo drug release, and deliver therapeutic biomolecules to the implant site, which in turn can trigger specific tissue responses or prevent the development of infection or inflammation.
[0109] Example 6
[0110] In addition to silk fibroin, other natural polymers such as hyaluronic acid, carboxymethyl cellulose and chitosan can also be made into conductive hydrogels by the same treatment method. Weigh a certain amount of hyaluronic acid, carboxymethyl cellulose and chitosan, dissolve them separately or mixed in 10mL 9.3M lithium bromide, add 200μL pyrrole and 400μL BDDE, mix well and remove bubbles, place in a 60℃ oven for reaction, and let stand for 3h to form gel. Then test the effects of other natural polymers and pyrrole at different ratios on the yield and conductivity of conductive hydrogels.
[0111] (1) Hyaluronic acid
[0112] According to the ratio of hyaluronic acid to pyrrole of 0.1g:200μL, 0.5g:200μL, 1g:200μL, 2.5g:200μL, and 5g:200μL, a certain amount of hyaluronic acid (molecular weight 140KDa) was weighed and dissolved in 10mL 9.3M lithium bromide, and 200μL pyrrole and 400μL BDDE were added and stirred quickly and evenly, and placed in a 60℃ oven for reaction for 3h.
[0113] The results showed that the above ratio of hyaluronic acid to pyrrole could form gels and crosslinks in 9.3M lithium bromide. As the amount of hyaluronic acid added increased, the yield of conductive hydrogel also increased. When 5g of hyaluronic acid was added to the system, the yield was 15 times that of the initial state. Figure 6 The conductivity also shows the same trend as the yield. When the amount of hyaluronic acid added in the system increases, more pyrrole molecules interact with hyaluronic acid under the action of hydrogen bonds between hyaluronic acid and pyrrole, and then through the oxidation of lithium bromide in the system, a denser polypyrrole conductive pathway is formed, and the conductivity therefore increases accordingly.
[0114] (2) Carboxymethyl cellulose
[0115] According to the ratio of carboxymethyl cellulose and pyrrole of 0.001g:200μL, 0.01g:200μL, 0.05g:200μL, 0.1g:200μL, 0.2g:200μL, 0.3g:200μL, and 0.5g:200μL, a certain amount of carboxymethyl cellulose was weighed and dissolved in 10mL 9.3M lithium bromide, and 200μL pyrrole and 400μL BDDE were added, stirred quickly and evenly, and placed in a 60℃ oven to react for 3h.
[0116] The results show that at the above ratio of carboxymethyl cellulose to pyrrole, the conductive hydrogel can be cross-linked in 9.3M lithium bromide. As the amount of carboxymethyl cellulose added increases, the color of the conductive hydrogel gradually darkens and the conductivity increases. However, excessive addition of carboxymethyl cellulose (greater than or equal to 0.5 g) will make the conductive hydrogel turbid. Figure 7 As shown (the amount of carboxymethyl cellulose added from left to right is 0.1g, 0.2g, 0.3g, and 0.5g), it may be that the points for forming hydrogen bonds between carboxymethyl cellulose and pyrrole molecules have all been satisfied, and there are too many molecules forming hydrogen bonds between cellulose, resulting in this phenomenon.
[0117] (3) Chitosan
[0118] According to the ratio of chitosan to pyrrole of 0.1g:200μL, 0.5g:200μL, 1g:200μL, 2.5g:200μL, and 5g:200μL, a certain amount of chitosan was weighed and dissolved in 10mL 9.3M lithium bromide, and 200μL pyrrole and 400μL BDDE were added and stirred quickly and evenly, and placed in a 60℃ oven for reaction for 3h.
[0119] The results showed that at the above ratio of chitosan and pyrrole, gelation and cross-linking can be formed in 9.3M lithium bromide. With the increase of chitosan addition, the hydrogen bonding between chitosan and polypyrrole, and the interpenetration between excess chitosan molecules, chemical and physical cross-linking gave the conductive hydrogel higher mechanical properties. Figure 8 CS / PPy is a hydrogel formed by chitosan and pyrrole (the ratio of chitosan to pyrrole is 1 g:200 μL), and CS is a hydrogel formed by chitosan.
[0120] The study found that the gelling effect under the above conditions is relatively good and has a certain elasticity. This is because the high molecular polymer dissolved in the lithium bromide system can expose more reactive groups and undergo a cross-linking reaction with the BDDE ring opening, and polypyrrole can form hydrogen bonds with the remaining amino and carboxyl groups on the high molecular polymer molecular chain, obtaining better compression performance than without the introduction of pyrrole. The addition of the above materials can prepare conductive hydrogels that meet the requirements.
[0121] The inventors conducted experiments on one or more natural high molecular weight polymers with other molecular weights and modifications according to the experimental scheme of the above embodiment, and obtained experimental phenomena and conclusions similar to those of embodiment 1.
[0122] The inventors conducted experiments according to the experimental scheme of the above embodiments on diglycidyl ethers, such as diglycidyl ether, 1,4-butanediol diglycidyl ether (BDDE), 1,3-diglycidyl ether glycerol, bisphenol A diglycidyl ether and its derivatives, resorcinol diglycidyl ether, tris(4-hydroxyphenyl)methane triglycidyl ether, and neopentyl glycol diglycidyl ether, or various combinations thereof, and obtained experimental phenomena and conclusions similar to those in Example 1.
[0123] Example 7
[0124] The conductive hydrogel cross-linking reaction conditions screened in Example 3 were as follows: a silk fibroin concentration of 200 mg / mL, a silk fibroin to BDDE ratio of 1 g:200 μL, a reaction system lithium bromide concentration of 9.3 M, and a silk fibroin to pyrrole ratio of 1:250 g / μL to prepare a silk fibroin solution and a BDDE mixture, and the mixture was immediately added dropwise as an aqueous phase into the oil phase that had been preheated at 60°C and was in a moving state.
[0125] The oil phase movement speed was fixed at 500rpm, and the oil-water ratio was changed to 1:1, 2:1, 5:1, 10:1, 100:1, and 500:1. After the oil phase and the water phase were mixed evenly, they were placed in a 60°C oven for reaction for 3 hours to observe whether spherical gel was formed in the reaction system. The results showed that when the oil-water ratio was 1:1 and 2:1, the gel was in block form. Due to the large volume of the water phase, the spacing between the rounded gel balls formed in the moving oil phase was too small, and the balls were easily aggregated. The incompletely cross-linked gel ball aggregates gradually cross-linked to form block gels, rather than cross-linked gel balls. Gel balls can be formed when the oil-water ratio is 5:1, 10:1, 100:1, and 500:1. Considering the granulation efficiency, the inventor believes that the oil-water ratio of 10:1 is the best reaction condition.
[0126] The ratio of the oil phase to the water phase was fixed at 10:1, and the speed of the oil phase movement was changed: 50rpm stirring, 100rpm stirring, 500rpm stirring, 1000rpm stirring, 5000rpm homogenization, and 10000rpm homogenization. After the oil phase and the water phase were mixed evenly, they were placed in a 60°C oven for reaction for 3 hours to observe whether gel balls were formed in the reaction system. The results showed that when the speed was 50rpm, due to the slow movement of the oil phase, the movement amplitude and frequency of the gel balls in the oil phase were too small, and the balls were very easy to collide and aggregate. The incompletely cross-linked gel ball aggregates gradually cross-linked to form block gels, rather than cross-linked gel balls. When the oil phase speed was 100rpm, 500rpm, 1000rpm, 5000rpm, and 10000rpm, gel balls could be formed.
[0127] The above gel balls were filtered out from the oil phase, and the surface oil was first washed with an organic solvent, and then washed with water, and the collected gel balls were filtered with sieves of different mesh sizes, and gel balls above 300μm, 100-300μm, and below 100μm were collected respectively, and freeze-dried and weighed to calculate the yield. The results showed that relatively ideal conductive silk fibroin hydrogel microspheres could be obtained in the range of 100-10000rpm. In the range of oil-water ratio greater than 1:1, relatively ideal conductive silk fibroin hydrogel microspheres could be obtained. In the range of oil-water ratio greater than 2:1-500:1, the performance of conductive silk fibroin hydrogel microspheres is even better.
[0128] Example 8
[0129] (1) Electrode coating
[0130] Although conductive polymers have significant potential as coatings for biomedical devices, they are often brittle when deposited as thin films and are susceptible to nonspecific deposition of cells and proteins (i.e., biofouling). However, their combination with conductive hydrogels effectively addresses these limitations, as the hydrogels can be molecularly engineered to prevent biofouling and have higher mechanical elasticity.
[0131] The silk fibroin conductive gel prepared according to Examples 1-4 is coated on the electrode surface, and the conductive hydrogel is used as an electrode coating for tissue interface engineering with enhanced biocompatibility of biomimetic implants. The biomimetic coating can theoretically reduce the effect of strain mismatch at the tissue interface, which will minimize the deposition of fibrous scar tissue and improve device function.
[0132] (2) Drug delivery
[0133] Despite their inherent insulating properties, the porous structure and high water content of hydrogels provide a unique ability to load bioactive molecules or drugs into polymer networks. In addition, conductive hydrogels respond to applied electric fields by swelling, shrinking, bending, or other structural changes due to small differences in the electric potential across the hydrogel. Hydrogels based on hyaluronic acid, carboxymethyl cellulose, and chitosan have inherently electroactive properties due to the presence of acidic or basic ionic groups in the polymer network. However, their low electrical responsiveness and poor mechanical properties limit their application in implantable smart systems for long-term drug delivery.
[0134] According to the silk fibroin conductive gel prepared in Examples 1-4 or the silk fibroin conductive gel sphere prepared in Example 7, drugs are added during the gelation process, or drugs are adsorbed by dialysis after the gelation. The conductive hydrogel (sphere) with enhanced mechanical and conductive properties allows the development of electrically controlled drug release devices. Conductive hydrogels (spheres) can also be used to deliver antibacterial agents to prevent the occurrence of implant site infection. The release curve and diffusion rate of the drug depend on the cross-linking rate, PPy polymer size, electric field strength and electrode polarity. Conductive hydrogels (spheres) can also be used to deliver anti-inflammatory drugs to improve the long-term biocompatibility of implanted biomedical devices.
[0135] (3) Tissue Engineering
[0136] Conductive hydrogels can be used as scaffolds to simulate biological functions and induce cell proliferation, differentiation and migration in vitro and in vivo to promote the regeneration of excitable tissues. RMSCs were seeded on the conductive hydrogels prepared in Examples 1-4.
[0137] Experiments have shown that conductive hydrogels promote the adhesion and growth of RMSCs, and fluorescent images show uniform, dense and highly arranged cell organization, as well as enhanced cytoskeletal arrangement and cell connectivity. Conductive hydrogels can also regulate the proliferation and differentiation of some cells, such as osteoblasts MC3T3-E1 for bone tissue engineering and human primary skin fibroblasts for wound healing.
[0138] In addition, the subcutaneous implantation experiment in rats proved that the conductive hydrogel prepared by Examples 1-4 has high biocompatibility in vivo. Conductive hydrogels can affect stem cells and / or nerve cells under the action of an electric field in vitro, and have significant advantages in the structure and interface of designed heterocellular neural tissues implanted in vivo. Not only that, silk fibroin hydrogels can also be used to design bioactuators, convert electrical stimulation into mechanical force, and then used as bionic muscle fibers to develop transparent and deformable touch sensors, suitable for emerging applications such as bionic skin, and flexible / wearable biomedical devices.
[0139] The above detailed description of the present invention is intended to enable persons familiar with the art to understand the contents of the present invention and implement them. It does not limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A conductive hydrogel, characterized in that: Pyrrole and natural high molecular polymer are cross-linked in the presence of lithium bromide and a cross-linking agent to form a conductive hydrogel with a tissue-acceptable carrier, wherein the conductive hydrogel does not contain a strong oxidant; the natural high molecular polymer is one of silk fibroin, carboxymethyl cellulose, hyaluronic acid and chitosan; and the cross-linking agent is selected from one or more of diglycidyl ethers.
2. The conductive hydrogel according to claim 1, characterized in that: When the natural polymer is silk fibroin, the mass volume ratio of the natural polymer to the pyrrole is 1g: (100~2500) μL; when the natural polymer is carboxymethyl cellulose, the mass volume ratio of the natural polymer to the pyrrole is 1g: (400~2000) μL; when the natural polymer is hyaluronic acid, the mass volume ratio of the natural polymer to the pyrrole is 1g: (40~2000) μL; when the natural polymer is chitosan, the mass volume ratio of the natural polymer to the pyrrole is 1g: (40~2000) μL.
3. The conductive hydrogel according to claim 1, characterized in that: The strong oxidant includes one or more of ferric chloride, ammonium persulfate, potassium persulfate, and sodium persulfate.
4. The conductive hydrogel according to claim 1, characterized in that: The diglycidyl ethers include diglycidyl ether, 1,4-butanediol diglycidyl ether, 1,3-diglycidyl ether glycerol, bisphenol A diglycidyl ether and its derivatives, resorcinol diglycidyl ether, tris(4-hydroxyphenyl)methane triglycidyl ether and neopentyl glycol diglycidyl ether.
5. The conductive hydrogel according to claim 1, characterized in that: The mass volume ratio of the natural high molecular polymer to the cross-linking agent is 1 g: (150-300) μL.
6. A method for preparing a conductive hydrogel according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: (1) preparing a solution containing pyrrole, natural high molecular polymer and lithium bromide; (2) adding a crosslinking agent to the solution to form a conductive hydrogel by crosslinking; The conductive hydrogel does not contain a strong oxidant.
7. The preparation method according to claim 6, characterized in that: The lithium bromide is fed in the form of a lithium bromide aqueous solution, the mass volume ratio of the natural high molecular polymer to the lithium bromide aqueous solution is (0.5-400) mg:1 mL, and the concentration of the lithium bromide aqueous solution is 1-10M.
8. The preparation method according to claim 6, characterized in that: The step (1) specifically comprises: adding the natural high molecular polymer soaked in pyrrole into a lithium bromide aqueous solution, dissolving it at 4-80° C. for 10 min-72 h, and obtaining the solution.
9. The preparation method according to claim 6, characterized in that: In the step (2), the cross-linking temperature is 4-80° C.; and / or the cross-linking time is 10 min-72 h.
10. A method for preparing a conductive gel ball, characterized in that: The solution according to any one of claims 6 to 9 is mixed with a cross-linking agent, and then added to an oil phase system to carry out a cross-linking reaction under stirring conditions.
11. Use of the conductive hydrogel according to any one of claims 1 to 5 or the conductive gel ball prepared by the preparation method according to claim 10 in electrode coating, drug delivery or tissue engineering.
Citation Information
Patent Citations
Silk fibroin / carbon material conductive hydrogel as well as preparation and application thereof
CN113292744A
Chemical crosslinking hydrogel and microsphere, and preparation method and application thereof
CN113549227A
Preparation method of starch-based functional degradable conductive hydrogel
CN114957723A